Ob'yem i inten'sivnost' trenirovochnoi nagruzki y sil'neishchikh tyazheloatletok v zavisimosti ot etapa podgotovki na sovremennom etape - Medvedev, A. S. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this study was to analyze the structure of training loadings realizing in the training process of elite women-weignt-lifters. The results in international competitions were also analyzed, es well the training loads of the athletes of different countries (China, Bulgaria, Russia).